Adaptation of Organisational Climate Description Questionnaire (OCDQ-RS) - Peter Gavora; Jarmila Braunová (Czech Pedagogical Society, 2010)
The paper describes the adaptation of Organisational Climate Description Questionnaire(OCDQ-RS) for the Slovak educational environment. It explains the processof the adaptation step by step including some problems that occurred in the adaptation.In contrast with the original American version, the final Slovak form of the questionnairehas more than two-thirds of new items, two original items were placed in differentdimensions, and two dimensions have different number of items when compared withthe American form. Findings from four schools are presented in each of the dimensions,and it is demonstrated how the main characteristics - open climate index - was affectedby individual dimensions of the questionnaire.